STUDY OF AGRICULTURAL IRRIGATION WATER QUALITY ON RICE (Oryza sativa L.) PRODUCTIVITY IN PATEBON VILLAGE, PASURUAN REGENCY - Rally Murthi; Ahmad Zainul Arifin; Retno Tri Purnamasari; Fajar Hidayanto (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
Irrigation water quality is an important factor in rice productivity, especially in areas receiving water from polluted rivers. This study aims to analyze the status of irrigation water quality and its impact on rice productivity in Patebon Village, Pasuruan Regency, which is fed by the Welang Watershed through the Sendupati and Depok Rivers. The study was conducted from September 2024 to January 2025 using a quantitative descriptive method with a survey approach. Water sampling was carried out purposively at six points (upstream, midstream, and downstream) in May and August 2024. Eight parameters were analyzed: pH, TSS, DO, BOD, COD, nitrate, phosphate, and E. coli bacteria. Water quality status was determined using the Pollution Index (IP) method based on the Decree of the Minister of Environment No. 115 of 2003. The results showed that in 2024, the IP value ranged from 0.92 to 1.50. Most of the sample points (points 2–6) are in the lightly polluted category (class II), except for downstream point 1 which is in the good category (class I). Rice productivity in Patebon Village increased from an average of 3.3 quintals/land area in 2022 to 5.6 quintals/land area in 2024. Despite the increase in productivity, physical parameters such as TSS, DO, BOD, and COD in 2022 were still classified as class III, indicating an improvement in water quality in 2024. A decrease in IP value of 60.3% at the midpoint indicates an improvement in water quality that is correlated with an increase in crop yields. This study recommends the need for sustainable pollution control to maintain agricultural sustainability. Keywords: rice, water quality, harvest yield, pollution index